2008
DOI: 10.1002/cphc.200800590
|View full text |Cite
|
Sign up to set email alerts
|

Does the Surface Matter? Hydrogen‐Bonded Chain Formation of an Oxalic Amide Derivative in a Two‐ and Three‐Dimensional Environment

Abstract: We report on a multi‐technique investigation of the supramolecular organisation of N,N‐diphenyl oxalic amide under differently dimensioned environments, namely three‐dimensional (3D) in the bulk crystal, and in two dimensions on the Ag(111) surface as well as on the reconstructed Au(111) surface. With the help of X‐ray structure analysis and scanning tunneling microscopy (STM) we find that the molecules organize in hydrogen‐bonded chains with the bonding motif qualitatively changed by the surface confinement. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
31
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 79 publications
2
31
0
1
Order By: Relevance
“…[14] Furthermore on close-packed noble metal surfaces the interaction between phenyl rings and the substrate is relatively weak, such that reorientations of rotatable phenyl moieties are possible. [24] Note that a lift from the surface in cluster formation was already demonstrated in ab initio calculations for adsorbed benzonitrile. [16] In Figure 4 a the coverage is about 0.1 ML.…”
Section: Resultsmentioning
confidence: 87%
“…[14] Furthermore on close-packed noble metal surfaces the interaction between phenyl rings and the substrate is relatively weak, such that reorientations of rotatable phenyl moieties are possible. [24] Note that a lift from the surface in cluster formation was already demonstrated in ab initio calculations for adsorbed benzonitrile. [16] In Figure 4 a the coverage is about 0.1 ML.…”
Section: Resultsmentioning
confidence: 87%
“…23 N,N-Diphenyloxalic amide self-assembles into a chain structure based on N-H/O hydrogen bonds. 24 Apparently, intrinsic Ag adatoms are not reactive enough to coordinate supramolecular building blocks through their nitrogen atoms. Since in the present study contrast features that hint towards coordinating Ag atoms have never been observed and the experimental intermolecular bond distances are consistent with a mere hydrogen bond scenario, formation of metalcoordination bonds can be excluded.…”
Section: Resultsmentioning
confidence: 99%
“…NEXAFS is sensitive to the adsorption angle α of a specifi c molecular moiety (as defi ned the ordering of the fi rst monolayers depends strongly on the underlying substrate but for thick enough multilayer fi lms, a bulk-like structure prevails. [ 22 , 23 ] For molecules with stronger intermolecular forces due to functional groups like perylenetetracarboxylic-dianhydride [ 24 ] or biphenyl-oxalic amide, [ 25 ] the transition to the bulk ordering takes place even faster. The use of strongly corrugated substrates such as Cu(110) and its oxygen-covered variant allowed controlling the azimuthal alignment of sexithiophene [ 26 ] and the afore mentioned sexiphenyl, [ 9 ] but in both cases only minor changes to the bulk-like ordering could be achieved in the thin fi lms.…”
Section: Introductionmentioning
confidence: 99%